2011
DOI: 10.2174/2210289201102010104
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Polyethylene Glycol (PEG)

Abstract: Covalent attachment of polyethylene glycol (PEG) to active proteins (PEGylation technology) successfully generated several FDA-approved compounds, including four blockbusters, which are considered non immunogenic. However, PEG antibodies and intolerance to the infusion were reported in some patients with gout treated with pegloticase, a PEG-uricase recently approved by the FDA (Food and Drug Administration, USA). Therefore, we reviewed the literature concerning immunogenicity of PEG alone or covalently attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Animal studies have also reported the formation of anti-PEG antibodies on the administration of PEGylated proteins. For example, anti-PEG antibodies have been observed in the case of PEG-uricase and PEG-asparaginase resulting in a more accelerated clearance of the conjugate [163][164][165]. These are hyper-PEGylated examples with many PEG chain ends available to elicit an immune response.…”
Section: Alternatives To Pegmentioning
confidence: 99%
“…Animal studies have also reported the formation of anti-PEG antibodies on the administration of PEGylated proteins. For example, anti-PEG antibodies have been observed in the case of PEG-uricase and PEG-asparaginase resulting in a more accelerated clearance of the conjugate [163][164][165]. These are hyper-PEGylated examples with many PEG chain ends available to elicit an immune response.…”
Section: Alternatives To Pegmentioning
confidence: 99%
“…PEG is often used as the hydrophilic block in block copolymers because a wide range of molecular weights are readily available and the resulting assemblies in water display PEG chains on the surface of the nanocarrier that delay the physisorption of serum proteins. Despite growing evidence of immunological responses to PEG (36, 37) that can in principle limit therapeutic efficacy, it remains a widely used hydrophilic polymer in drug formulations. Attractive alternatives include zwitterionic polymers (38) that are just emerging in polymersome applications to tumors (39).…”
Section: Nanocarrier Designmentioning
confidence: 99%
“…In addition to these hydrophobic issues, PEG also suffers oxidation damage in biological media for long-term applications [5,26,34,[44][45][46]. Furthermore, PEG antibodies occur in animals [15,34,47,48] and even humans [48], complicating clinical trials involving this material.…”
Section: Introductionmentioning
confidence: 99%